Induction of photosynthesis under anoxic condition in Thalassiosira pseudonana and Euglena gracilis: interactions between fermentation and photosynthesis - Gain, Gwenaëlle; Berne, Nicolas; Feller, Tom; Godaux, Damien; Cenci, Ugo; Cardol, Pierre (Frontiers in Plant Science, 2023)
In their natural environment, microalgae can be transiently exposed to hypoxic or anoxic environments. Whereas fermentative pathways and their interactions with photosynthesis are relatively well characterized in the green alga model Chlamydomonas reinhardtii, little information is available in other groups of photosynthetic micro-eukaryotes. In C. reinhardtii cyclic electron flow (CEF) around photosystem (PS) I, and light-dependent oxygen-sensitive hydrogenase activity both contribute to restoring photosynthetic linear electron flow (LEF) in anoxic conditions. Here we analyzed photosynthetic electron transfer after incubation in dark anoxic conditions (up to 24 h) in two secondary microalgae: the marine diatom Thalassiosira pseudonana and the excavate Euglena gracilis. Both species showed sustained abilities to prevent over-reduction of photosynthetic electron carriers and to restore LEF. A high and transient CEF around PSI was also observed specifically in anoxic conditions at light onset in both species. In contrast, at variance with C. reinhardtii, no sustained hydrogenase activity was detected in anoxic conditions in both species. Altogether our results suggest that another fermentative pathway might contribute, along with CEF around PSI, to restore photosynthetic activity in anoxic conditions in E. gracilis and T. pseudonana. We discuss the possible implication of the dissimilatory nitrate reduction to ammonium (DNRA) in T. pseudonana and the wax ester fermentation in E. gracilis.